The impact of traditional Chinese medicine on gastrointestinal dysfunction in sepsis patients: a systematic review and network meta-analysis - Sang, Ziyi; Wang, Yuchao; Wu, Caixia; Yin, Jiangtao (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate, via a network meta-analysis, the efficacy and comparative differences of 16 traditional Chinese medicines—including Dachaihu Tang, Tiaoqi Tongfu Tang, Yiqi formulations, Dahuang Fuzi Tang, and Xuebijing—in treating gastrointestinal dysfunction in patients with sepsis. Effect sizes were quantified across outcome measures such as gastrointestinal dysfunction scores, traditional Chinese medicine syndrome scores, APACHE II scores, AGI grades, mean levels of D-lactate, diamine oxidase (DAO), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and intra-abdominal pressure (IAP), with the aim of providing evidence-based recommendations for precise clinical medication.MethodsRandomized controlled trials assessing the efficacy of various traditional Chinese medicines in patients with sepsis-induced gastrointestinal dysfunction were retrieved by systematically searching PubMed, Embase, Cochrane Library, Web of Science, and CNKI.ResultsTraditional Chinese medicines were overall more effective than conventional treatments in improving gastrointestinal function, suppressing inflammatory responses, and repairing the intestinal mucosal barrier in patients with sepsis. Among the evaluated formulas, Dachaihu Tang showed the most significant improvement in gastrointestinal dysfunction scores [MD = −2.03, 95% CI: −3.86 to −0.20], while Yiqi formulations exhibited the most favorable effect on traditional Chinese medicine syndrome scores [MD = −5.70, 95% CI: −9.84 to −1.56]. Dahuang Fuzi Tang was most effective in improving AGI grade [MD = 0.27, 95% CI: 0.19 to 0.40], and Tiaoqi Tongfu Tang had the strongest effect on reducing IAP [MD = −4.93, 95% CI: −9.09 to −0.77]. In terms of inflammatory markers, Tiaoqi Tongfu Tang significantly reduced APACHE II scores [MD = −6.90, 95% CI: −9.66 to −4.13] and TNF-α levels [MD = −7.65, 95% CI: −10.27 to −5.04], while Houpo Heji had the most potent regulatory effect on IL-6 [MD = −4.24, 95% CI: −5.34 to −3.14]. Regarding intestinal mucosal barrier repair, Xuebijing was most effective in reducing D-lactate levels [MD = −3.51, 95% CI: −6.73 to −0.29], and had the greatest effect on improving DAO levels [MD = −4.57, 95% CI: −7.86 to −1.28].ConclusionThis study provides an evidence-based reference for clinical decision-making. Different traditional Chinese medicines demonstrated distinct advantages in the treatment of gastrointestinal dysfunction associated with sepsis. It is recommended that clinical interventions be selected based on core pathological features: Dachaihu Tang for gastrointestinal motility disorders, Tiaoqi Tongfu Tang and Houpo Heji for prominent systemic inflammatory responses, and Xuebijing for severe mucosal barrier damage. All of these treatments showed significant superiority over conventional therapies. These findings require further validation through longer-duration, larger-sample, and higher-quality randomized controlled trials.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251062621, identifier CRD420251062621.